(untitled) (SciComm Report, 2022)
There is wide evidence on the relevance of both awareness and policymaking in coping with environmental progressive deterioration. With 6,435 km of coastline, Chile has one of the longest and most diverse marine ecosystems in the world. It is believed that a greater understanding of the marine environment is likely to make citizens feel responsible to act as stewards of the ocean. But knowledge is not everything, since we have personal values, attitudes and perceptions that are also an important part of active marine citizenship. In this study we answer the question: does a deeper connection with the ocean means having more knowledge about ocean issues? Our results showed that, on average, our basic knowledge about the ocean is very limited even when feeling a strong connection with it. Research into knowledge plus perceptions towards the marine environment can aid in designing the most effective learning experiences.